Development of CO₂ capture capacity by using impregnation method in base condition for K2CO3/Al2O3 - Jaruwan Charoenchaipet; Pornpote Piumsomboon; Benjapon Chalermsinsuwan (Energy Reports, 2020)
Carbon dioxide adsorbent is an important factor in the adsorption process of carbon dioxide. Therefore, this study interested in the adsorption of potassium carbonate solid sorbents on gamma-alumina to adsorb carbon dioxide. The added basic solution was used instead of the de-ionized water by assuming that it would give higher support surface area. The various preparation parameters were explored by impregnation method as follows: the different base types (NaOH, Ca(OH)2, and Na2CO3), the basicity of the solution (8, 10 and 12) and the duration of shaking (12, 18 and 24~h). From the results, all parameters affected on the carbon dioxide capture capacity. The sodium hydroxide gave the highest carbon dioxide capture capacity. An increasing in basicity of the solution resulted in higher carbon dioxide capture capacities, since the reactant was acidic. For the effect of the time spent on shaking the adsorbent, the ability to capture carbon dioxide increased with preparation time. The highest adsorption capacity of 4.34 mmol CO2 / g sorbent was obtained from potassium carbonate adsorbent, prepared by using sodium hydroxide with a pH value of 12 and a duration of 24~h while, in normal preparation condition, potassium carbonate adsorbent had a capacity of 2.27 mmol CO2 / g sorbent.
Keywords: 330; Base condition; CO2 capture capacity; Impregnation; K2CO3/Al2O3